Comparison of Antibacterial Ability of Anatase and Rutile TiO2 Thin Films - Tongwanichniyom, Suree; Buranawong, Adisorn; Juntaropakorn, Methee (Burapha Science Journal, 2026)
This research studied the nano–structured titanium dioxide (TiO2) thin films that had been coated on the silicon and glass slides by the reactive DC magnetron sputtering technique to compare the antibacterial ability of the TiO2 thin films between the anatase and rutile phases. After coating, the films were analyzed by various techniques. The crystal structures of coated samples were analyzed by the X–ray Diffraction (XRD), the microstructure surface and thickness were analyzed by the Field Emission Scanning Electron Microscope (FE–SEM), and the measurements of the optical transmission were analyzed by the UV–Visible Spectrophotometer. The results showed that the phases of the coated films varied with the total pressure while coating. The pressure increased from the rutile phase to the anatase phase. The crystal size of TiO2 thin films of the anatase phase was 43 nm, and the thickness was 150 nm. Also, the transmission in the visible range was approximately 75%. The surface had been formed and became tapered grains, and the grains spread over the surface of the film. There were deep grooves between grains. It could be observed from the FE–SEM. Meanwhile, the crystal size of TiO2 thin films of the rutile phase was 20 nm, and the thickness was 143 nm. The transmission in the visible range was approximately 65%. The surface had been formed in small and rounded grains. Then, they continuously spread across the surface of the film, and there were no deep grooves between grains. The comparasion of the antibacterial ability between Escherichia coli and Staphylococcus aureus with photocatalysis using the ultraviolet type A (UVA) found that the glass slides coated with the TiO2 thin films of the anatase and rutile phases had increased the antibacterial ability with time of the UVA irradiation. Moreover, TiO2 thin films of the anatase phase were more effective in disinfection than those of the rutile phase, and the TiO2 thin films of anatase phase was able to inhibit Escherichia coli better than Staphylococcus aureus.